Wear characteristics and machining studies on AZ31-calcium silicate composites - Kumar, Gandi Siva; Rambabu, Govada; Singaiah, Kanumuri; Sunil, B. Ratna (Edelweiss Applied Science and Technology, 2025)
Composites of AZ31 magnesium (Mg) alloy dispersed with calcium silicate were produced through friction stir processing (FSP) to investigate the effects of grain refinement and reinforcement on mechanical performance, wear resistance, and machining characteristics. Microstructural analyses and X-ray diffraction studies revealed significant grain refinement, reducing grain size from 114 ± 5.8 µm to 3.5 ± 1.4 µm, along with the development of a basal-dominated texture in the composites. The increased hardness, measured at 96.6 ± 7.5 HV0.1, was higher than that of the base AZ31 alloy, which was 59.2 ± 6.4 HV0.1. This enhancement is attributed to grain refinement and the addition of calcium silicate. Wear tests demonstrated a lower coefficient of friction and improved wear resistance, correlating with the increased hardness of the composite material. Machining studies conducted at drilling speeds of 90 rpm and 180 rpm, with feeds of 15 mm/min and 30 mm/min, showed increased cutting forces for the composite. This increase is likely due to the enhanced mechanical strength resulting from the fine-grained structure and the presence of ceramic phases within the composite. The study concludes that AZ31-calcium silicate composites exhibit superior mechanical properties and wear resistance. However, the increased difficulty in machining presents a challenge, which must be considered when designing processes involving AZ31-calcium silicate structures for machining applications.